Political polarization and the size of government - Erik Lindqvist; Robert Östling (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
We study the effect of political polarization on public spending using the dispersion of self-reported political preferences as our measure of polarization. Political polarization is strongly associated with smaller government in democratic countries, but there is no relationship between polarization and the size of government in undemocratic countries. The results are robust to a large set of control variables, including GDP per capita and income inequality.
Keywords: H10; H20; H41; 330; Political polarization; social cohesion; size of government; redistribution; Sozialer Indikator; Regierung; Wirtschaftslage; Vertrauen; Welt; Soziale Beziehungen